Eating soup with nails of pig: thematic synthesis of the qualitative literature on cultural practices and beliefs influencing perinatal nutrition in low and middle income countries. Issue 1 (December 2016) - Raman, Shanti; Nicholls, Rachel; Ritchie, Jan; Razee, Husna; Shafiee, Samaneh
Abstract Background The perinatal period, i.e. pregnancy, childbirth and early infancy, is a significant transition period where the biological and the social strongly intersect. In low and middle-income countries the disease burden arising from the perinatal period, is still substantial. The perinatal period is also a crucial window of opportunity for reducing undernutrition and its long term adverse effects. Methods We explored qualitative research conducted in low resource settings around the perinatal continuum over the past two decades, with a particular focus on the 'cultural' realm, to identify common themes influencing maternal and infant nutrition. We systematically searched electronic databases from 1990 to 2014, including MEDLINE, EMBASE, PsycINFO, Scopus and Cumulative Index to Nursing and Allied Health Literature, using relevant search terms including traditional beliefs, practices, pregnancy, childbirth, developing countries etc. Adapted Consolidated Criteria for Reporting Qualitative Health Research and Critical Appraisal Skills Programme criteria were used to determine quality of studies. We synthesised the literature thematically, enabled by NVivo 10 software. Results Most studies showed cultural support for breastfeeding, although most traditional societies delayed breastfeeding due to colostrum being considered 'dirty'. A range of restrictive practices through pregnancy and the post- partum period were revealed in Asia, Latin America and Africa. There was a strong cultural understanding of the healing power of everyday foods. A wide range of good foods and bad foods continued to have currency through the perinatal continuum, with little consensus between groups of what was beneficial versus harmful. Cross-cutting themes that emerged were 1) the role of the woman/mother/wife as strong and good; 2) poverty restricting women's nutrition choices; 3) change being constant, but the direction of change unpredictable. Conclusions A rich and diverse repertoire of cultural practices and beliefs influenced perinatal nutrition. Results from this synthesis should influence public health policymakers and practitioners, to tailor contextually specific, culturally responsive perinatal nutrition interventions to optimise health and wellbeing of mother-infant dyads. Ideally these interventions should build on culturally sanctioned life affirming behaviours such as breastfeeding, promoting post-partum rest and recovery, while modifying the potentially harmful aspects of other cultural practices in the perinatal period.